The internalization of religious moderation values in aqidah and akhlaq courses at the Faculty of Tarbiyah and Teacher Training (FTIK) of IAIN Kerinci - Pohan, Muhammad Munawir; Wisda, Rini Syevyilni (STAI Auliaurrasyidin Tembilahan, 2024)
The diversity of Indonesian society is reflected in the variety of ethnicities, religions, races, and social groups spread across the archipelago. Religious moderation is recognized as a key approach to addressing issues of radicalism and extremism. This study aims to gain a comprehensive understanding of the process of incorporating religious moderation values into the curriculum for students in the Islamic Education Management Department at IAIN Kerinci, Jambi Province. The research employs a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The validity of the data was ensured through internal validity measures, including data triangulation, member checking, repeated observations at the research site, peer debriefing, involvement of informants in various stages of the research, and researcher bias clarification. The results reveal that the teaching style of lecturers at the Faculty of Tarbiyah and Teacher Training (FTIK) of IAIN Kerinci plays a crucial role in shaping students to become moderate, tolerant, and peace-loving individuals. Lecturers employ interactive and participatory teaching approaches, integrating religious moderation values into the curriculum using various instructional methods. Factors contributing to the internalization of these values among students include participation in extracurricular activities and campus organizations that promote interfaith dialogue, as well as involvement in social service activities with communities of different religious backgrounds.